(untitled) (REMUNOM, 2025)
Throughout organizational history, strategies for recruiting and attracting talent to join the workforce have undergone significant transformations. The advent of the paradigm known as HR 4.0, characterized by the incorporation of innovative technologies and methodologies, represents a turning point in this digital transformation. This modern circumstance raises a considerable range of obstacles for business entities that aim to adapt to this new reality. Therefore, this study aims to present the main obstacles that HR specialists face when introducing innovative recruitment and selection practices, as well as the tactics used to overcome such barriers. The methodological architecture of this research is based on an analysis of specialized literature. The findings of this research reveal the most common obstacles that hinder the assimilation of recruitment 4.0, while also pointing out paths and strategies used to mitigate its impacts. Likewise, it highlights the crucial elements that require improvement to increase the efficiency and effectiveness of selection procedures. Therefore, we realize that putting HR 4.0 into practice still faces some major obstacles. The main one involves the money that needs to be invested in new technologies, the preparation of people who work in HR to deal with these new developments, and how to combine these digital tools with the routine of taking care of the team. Even with these obstacles, companies that approach these points with planning and care have a great chance of making their processes for finding and selecting people much better, faster, and aligned with what the job market currently demands in this new era.